An analysis of the competitive business environment of a family run Brazilian auditing firm. (1st January 2013) - Trieloff, Werner; Buys, Pieter W.
The growing reality of globalisation has contributed too many new challenges in the auditing and related services industries, which placed more pressure on audit firms' of all sizes drive for long-term sustainability. Just like their global counterparts, audit firms in the Brazilian marketplace also need to be cognisant of its own competitive business environment in order to survive in a very competitive environment. However, in such a dynamic business environment, organisational resilience becomes a crucial building block in achieving sustainability. The key objective of this article is to identify and consider key factors in the competitive environment of an established nationally-based Brazilian audit firm, that not only embraces a thorough understanding of its business environment, but also of resilient strategies to support the firm's long-term sustainability. Based on a PEST and SWOT analysis, it was found that the firm's internal competencies and business environment, as well as the unpredictable role of government together complex bureaucratic regulations, makes for both challenging and promising times in the Brazilian auditing and related services industry.